Group of units of finite group algebras of groups of order 24 - Sahai, M.; Ansari, S. F. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5Let $F$ be a finite field of characteristic $p.$ The structures of the unit groups of group algebras over $F$ of the three groups $D_{24},$ $S_4$ and $SL(2, \mathbb{Z}_3)$ of order $24$ are completely described in numerous works. We present the unit groups of the group algebras over $F$ for the remaining groups of order $24,$ namely, $C_{24},$ $C_{12} × C_2,$ $C_2^3 × C_3,$ $C_3 \rtimes C_8,$ $C_3 \rtimes Q_8,$ $D_6 × C_4,$ $C_6 \rtimes C_4,$ $C_3 \rtimes D_8,$ $C_3 × D_8,$ $C_3 × Q_8,$ $A_4 × C_2,$ and $D_{12} × C_2.$